주파수 전달함수를 이용한 신 포괄 곡선맞춤법 - 민천홍(Cheon-Hong Min); 박한일(Han-Il Park); 배수룡(Soo-Ryong Bae); 전재진(Jae-Jin Jeon) (Han-guk haeyang gonghak hoeji (Online), 2009)
Several damping materials have been employed to reduce the vibration of structures. While it is important to estimate the damping matrix when analyzing damped composite structures using the finite element method (FEM), at present, there is no FEM program that can correctly estimate the damping matrix. In this paper, a new global curve-fitting method is proposed for identifying the system parameters of non-proportional damping structures using a frequency response function. An experimental test for a cantilever beam attached damping material was carried out to verify the performance of the method proposed in this study.